Feasibility study of ultrasound imaging for stereotactic body radiation therapy with active breathing coordinator in pancreatic cancer. (2nd June 2017) - Su, Lin; Iordachita, Iulian; Zhang, Yin; Lee, Junghoon; Ng, Sook Kien; Jackson, Juan; Hooker, Ted; Wong, John; Herman, Joseph M.; Sen, H. Tutkun; Kazanzides, Peter; Lediju Bell, Muyinatu A.; et al.
Abstract: Purpose: Stereotactic body radiation therapy (SBRT) allows for high radiation doses to be delivered to the pancreatic tumors with limited toxicity. Nevertheless, the respiratory motion of the pancreas introduces major uncertainty during SBRT. Ultrasound imaging is a non‐ionizing, non‐invasive, and real‐time technique for intrafraction monitoring. A configuration is not available to place the ultrasound probe during pancreas SBRT for monitoring. Methods and Materials: An arm‐bridge system was designed and built. A CT scan of the bridge‐held ultrasound probe was acquired and fused to ten previously treated pancreatic SBRT patient CTs as virtual simulation CTs. Both step‐and‐shoot intensity‐modulated radiation therapy (IMRT) and volumetric‐modulated arc therapy (VMAT) planning were performed on virtual simulation CT. The accuracy of our tracking algorithm was evaluated by programmed motion phantom with simulated breath‐hold 3D movement. An IRB‐approved volunteer study was also performed to evaluate feasibility of system setup. Three healthy subjects underwent the same patient setup required for pancreas SBRT with active breath control (ABC). 4D ultrasound images were acquired for monitoring. Ten breath‐hold cycles were monitored for both phantom and volunteers. For the phantom study, the target motion tracked by ultrasound was compared with motion tracked by the infrared camera. For the volunteer study, the reproducibility of ABC breath‐hold was assessed. Results: The volunteer study results showed that the arm‐bridge system allows placement of an ultrasound probe. The ultrasound monitoring showed less than 2 mm reproducibility of ABC breath‐hold in healthy volunteers. The phantom monitoring accuracy is 0.14 ± 0.08 mm, 0.04 ± 0.1 mm, and 0.25 ± 0.09 mm in three directions. On dosimetry part, 100% of virtual simulation plans passed protocol criteria. Conclusions: Our ultrasound system can be potentially used for real‐time monitoring during pancreas SBRT without compromising planning quality. The phantom study showed high monitoring accuracy of the system, and the volunteer study showed feasibility of the clinical workflow.